DEVELOPMENT OF INTERACTIVE MEDIA-BASED WAVE TEACHING MATERIALS TO IMPROVE STUDENTS' PROBLEM AND PERFORMANCE CAPABILITY - Ahsani, Muh Syukri; Yulianto, Agus; Sarwi, Sarwi (Universitas Negeri Semarang, 2019)
This study aims to produce teaching materials to improve problem-solving skills that are feasible to use as a class XII physics learning media on sound wave material. In addition, it is also to find out the response of students to teaching materials developed in terms of meeting the standards of usability and quality. This research is R & D research with design according to Borg including: needs analysis, product planning and development, product development, product evaluation, and final products. The instructional materials developed have been implemented in 63 students of class XII SMAN 5 Semarang. Data collection is done by giving a validation sheet to the senior teacher. Data on students 'problem solving abilities were obtained from the results of the pretest and posttest while the students' performance was seen from the observation of practical activities in the laboratory. Students are also given a questionnaire to provide input on the teaching materials that have been developed. The results of the study indicate that the product of development is declared feasible based on expert judgment. Implementation of teaching materials in physics learning in sound wave material is able to improve problem solving skills and student performance.